Molecular Characterization of Streptococcus pneumoniae Type 4, 6B, 8, and 18C Capsular Polysaccharide Gene Clusters - Jiang, Sheng-Mei (American Society for Microbiology, 2001)
Capsular polysaccharide (CPS) is a major virulence factor in Streptococcus pneumoniae. CPS gene clusters of S. pneumoniae types 4, 6B, 8, and 18C were sequenced and compared with those of CPS types 1, 2, 14, 19F, 19A, 23F, and 33F. All have the same four genes at the 5′ end, encoding proteins thought to be involved in regulation and export. Sequences of these genes can be divided into two classes, and evidence of recombination between them was observed. Next is the gene encoding the transferase for the first step in the synthesis of CPS. The predicted amino acid sequences of these first sugar transferases have multiple transmembrane segments, a feature lacking in other transferases. Sugar pathway genes are located at the 3′ end of the gene cluster. Comparison of the four dTDP-l-rhamnose pathway genes (rml genes) of CPS types 1, 2, 6B, 18C, 19F, 19A, and 23F shows that they have the same gene order and are highly conserved. There is a gradient in the nature of the variation of rml genes, the average pairwise difference for those close to the central region being higher than that for those close to the end of the gene cluster and, again, recombination sites can be observed in these genes. This is similar to the situation we observed for rml genes of O-antigen gene clusters of Salmonella enterica. Our data indicate that the conserved first four genes at the 5′ ends and the relatively conserved rml genes at the 3′ ends of the CPS gene clusters were sites for recombination events involved in forming new forms of CPS. We have also identified wzx and wzy genes for all sequenced CPS gene clusters by use of motifs.